2000
DOI: 10.1046/j.1365-2141.2000.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of symptomatic parvovirus B19 infection by fibrin sealant used during surgery

Abstract: Summary. Human parvovirus B19 infection has been shown to be transmissible by blood and blood products and to result in transient aplastic crisis in patients with rapid red cell turnover. We report three cases of iatrogenic parvovirus B19 infection resulting from the use of the same batch of ®brin sealant under operation. Fibrin sealant, which is a typical haemostatic agent produced from blood, has been used during surgery. Human parvovirus is resistant to existing virusinactivating techniques, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(130 citation statements)
references
References 10 publications
0
127
0
3
Order By: Relevance
“…Parvovirus B19 may infrequently be transmitted by other blood-derived products such as platelets, intravenous immunoglobulin, fibrin products and clottingfactor preparations (Cohen et al, 1997;Erdman et al, 1997;Hino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Parvovirus B19 may infrequently be transmitted by other blood-derived products such as platelets, intravenous immunoglobulin, fibrin products and clottingfactor preparations (Cohen et al, 1997;Erdman et al, 1997;Hino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Risks of viral transmissions are well documented [137]. Hino et al reported three cases of parvovirus B19 transmission from the use of commercial fibrin sealants [138]. This demonstrated that dry heat viral inactivation was not an effective means to eradicate the parvovirus.…”
Section: Safety Of Fibrin Gluementioning
confidence: 99%
“…18,19 Human thrombin has generally replaced bovine sources in these preparations, because in 126 cases since 1955, patients exposed to bovine thrombin have acquired thrombin antibodies. [20][21][22] In addition, Hino and coworkers 23 reported three cases of iatrogenic parvovirus B19 transmission associated with commercial sealants.…”
Section: Humphreys Et Al 1378mentioning
confidence: 99%